The Organizational Independence of Internal Auditors in Ghana: Empirical Evidence from Local Government - Dawuda, Abudu; Aninanya, Gariba Oswald; Alnaa, Samuel Erasmus (Asian Journal of Economic Modelling, 2015)
The effectiveness of the internal audit units in the public sector in promoting good corporate governance and risk management depends on several factors including the level of organizational independence they enjoy. This study therefore, sought to investigate the organizational independence of the internal auditors in the local government sector in Ghana. Descriptive research method was employed. The study deployed multistage sampling method to select internal auditors and purposive sampling for external auditors from Ghana Audit Service. In all, a total of 120 questionnaires were administered to them, out of which only 90 questionnaires were completed and returned. The main finding of the study include among others: inadequate budget allocation, internal audit units are given low status, management determine the scope of internal audit work due to absence of internal audit charter. The most serious threats to internal auditors’ independence include intimidation and familiarity threats. The study concludes that, the organizational independence of the internal auditors in the local government sector is in danger. It recommends that every assembly should establish an effective and quality Audit Review Implementation Committee (ARIC) that would give necessary support to both internal auditors and external auditors. Each assembly should have its own Internal Audit Charter. The internal audit units also need to be supported with necessary logistics.